Filosofia e religião Grécia: dinâmica de ruptura e diálogo - Humphreys, Sally C. (Classica - Revista Brasileira de Estudos Clássicos, 1990)
One aspect of the problem we have been asked to examine can be formulated in the question: how does it come about, in the 'axial age', that men start to ask whether human social organization and political decisions should be dominated by religious imperatives, and start to compare the claims of differing religious and/or secular accounts of the cosmos. What I propose to do in this paper is to look at the dynamics of this process by analysing the impact on Greek (and especially Athenian) religious thought and practice, and on poetry, of the pressures towards secularization and rationalization wich we can discern in Greek culture in the period between c. 550 and 300 B. C.